Flexible Pavement Life Cycle Cost Analysis by Using Monte-Carlo Method and the Suggestions for Developing Countries - Vu Hoai, Nam; Nguyen Huu, Dung; Duy Tran, Hung (International Journal of Sustainable Construction Engineering and Technology, 2021)
Flexible road pavement plays an essential role in developing an effective, economic, and safe operation road network of any country. In Vietnam, a developing country, the selection of a suitable flexible pavement structure is always a challenge due to fiscal limitations. The traditional determinant method (TDM) by which pavement structures are selected mainly on the basis of initial construction costs and traffic load has been used for many years in the nation. This paper presents the use of Monte Carlo simulation to analyze the entire flexible pavement life cycle cost. Data including initial and maintenance costs and road user costs were collected from several different types of existing flexible pavement in Nghe An province, Vietnam. Random variations of several main inputs were explored in order to develop density distribution functions. These functions then were used as the bases for Monte Carlo simulation. One million simulation runs were implemented and the Net Present Values (NPVs) among pavement types were compared under the light of risk analysis. Research results showed that TDM method provided bias and uncertain results compared to that of Monte Carlo one. In terms of long- term pavement performance, a low-cost pavement structure should not always be considered as a wise selection. Some other suggestions for a developing country as Vietnam were also included.